Breast exposure reduction using organ-effective modulation on chest CT in Asian women. Issue 119 (October 2019) - Ota, Joji; Yokota, Hajime; Takishima, Hazuki; Takada, Akiyo; Irie, Ryosuke; Suzuki, Yuka; Nagashima, Takeshi; Horikoshi, Takuro; Chida, Koichi; Masuda, Yoshitada; Uno, Takashi
Highlights: Organ effective modulation reduces breast dose by up to 12.2%. The effect of organ effective modulation varies depending on body habitus. Organ effective modulation does not reduce diagnostic image quality. Abstract: Purpose: Organ-effective modulation (OEM) is a mechanism to reduce radiation dose to selected organs on computed tomography (CT). The purpose of this study was to measure radiation dose to the breast in Asian patients undergoing chest CT and to clarify the degree of exposure reduction. Method: We randomly selected 60 female patients undergoing non-contrast chest CT after breast cancer surgery. To measure radiation dose, an optically stimulated luminescence dosimeter had been attached directly to the gown over the nonoperated breast in 30 patients. Radiologists evaluated the image quality with and without OEM. In order to clarify the characteristics of OEM, the effects of angle and object size were measured using a phantom and an ionization chamber dosimeter. Results: The OEM group received 9.1 ± 1.9 mGy and the non-OEM group received 10.7 ± 2.4 mGy. OEM reduced the exposure by 12.2% ( P  <  0.01). OEM caused no reduction in diagnostic quality. In the phantom study, the results of the angle effect were 3.2%, 11.2%, 28.7%, 31.3, 25.9%, 14.9% and 6.0% dose reductions at −90, −60, −30, 0, 30, 60 and 90°, respectively. The effect of the subject thickness was 3.7%, 17.5%, 30.2%, 31.7%, and 34.1% at 16, 20, 24, 28 and 32 cm diameters, respectively. Conclusions: OEM is a useful mechanism for reducing radiation exposure to the breast without affecting diagnostic imaging quality. The reduction rate correlated negatively with body habitus.